DETERMINATION OF THE CRYOPROTECTIVE EFFECT OF N-METHYLACETAMIDE IN RABBIT SEMEN - Akarsu, Serkan Ali; Gungor, Ibrahim Halil; Acisu, Tutku Can; Cakir, Aslihan; Guler, Edanur; Koca, Recep Hakki; Yuce, Abrurrauf (Cryo Letters, 2023)
BACKGROUND: Amides are low molecular weight cryoprotectants. N-methylacetamide(MA) is one of the cryoprotectant agents in this group. OBJECTIVE: To investigate the cryoprotective effect of MA in rabbit semen. MATERIALS AND METHODS: For this purpose, six ejaculates from six New Zealand rabbits were collected and pooled using an artificial vagina. Pooled semen was divided into four equal parts and diluted with TCG+ egg yolk. CPA was added to form the following groups: Control with 6% DMSO; Group 1 with 1% MA; Group 2 with 2% MA; and Group 3 with 3% MA. After the addition of CPA, the semen eqilibration procedure was started. Sperm were then drawn into 0.25 mL straws, frozen by automatic semen freezing and stored in a liquid nitrogen container. Pipettes were thawed after 24 h and analyses were performed. RESULTS: Total, progressive and rapid motility values of the Control group were higher than those of the MA groups (p<005). However, there was no statistical difference between the Control and Group 2 in terms of these parameters. While there was no statistical difference between the groups in terms of acrosome damage and mitochondrial membrane potential, the best results were observed in Control, Group 2, Group 1 and Group 3, respectively. When we compared all groups, no difference was found in terms of MDA, CAT and GSH-Px. There was a statistical difference between Group 3 and the Control in terms of GSH level (p<0.05). CONCLUSION: DMSO appeared to be more useful for the cryopreservation of rabbit semen compared to MA.
Keywords: cryopreservation; flow cytometry; N-methylacetamide; rabbit; spermatozoon